Transmission power management for throughput maximization in harvesting enabled D2D network - Saleem, Umber; Qureshi, Hassaan Khaliq; Jangsher, Sobia; Saleem, Muhammad (2016 IEEE Symposium on Computers and Communication (ISCC), 2016)
Unlike traditional cellular networks, the multi-tier architecture of 5G networks supports Device-to-Device (D2D) communication, which allows devices to communicate with each other autonomously. Consequently, D2D-enabled Internet of Things (IoT) promise to provide higher bandwidth through frequency spectrum sharing. However, energy efficient operation of the network becomes a major challenge due to unattended operation of devices. In this study, we propose a solar energy harvesting based model for throughput maximization of an overlay in-band D2D network and consider an energy prediction model for optimal power management. Sum rate maximization problem subject to energy and power constraints is formulated for multiple D2D pairs and maximum achievable throughput is investigated by employing optimal power allocation at transmitters. The proposed model is analysed using real world solar energy harvesting data. The results show that consistently high throughput can be achieved by scheduling the energy arrival duration, while at the same time, energy inefficiency can also handled by optimal power allocation at the devices.